The Influence of Price Fairness, Promotion, and Perceived Ease of Use on the Repurchase Intention - Assyifa Nur Amanda Putri; Innocentius Bernarto (MEC-J (Management and Economics Journal), 2023)
This research aims to analyze the positive influence of price fairness, promotion, and perceived ease of use on repurchase intention. The survey method was used to analyze the results. Data collection technique was carried out through a questionnaire instrument. Purposive sampling was applied in this study. The sample size was determined to be 400 samples. Questionnaires were distributed to the buyers who had made purchases at Lazada at least twice. Data analysis technique employed the Partial least Square-Structural Equation Modeling (PLS-SEM) approach of the SmartPLS program. The research results reveal that price fairness, promotion, and perceived ease of use have positive effects on the repurchase intention.